GR management as an ESG transformation driver: Evidence from Russian companies - Victoria V. Savelieva; Anna S. Veselova (Управленец)
Forging government-business relationships is an important prerequisite for a country’s economic system to function efficiently. In sustainable development, such cooperation is especially relevant as the state is one of the key stakeholders for business survival and responsible corporate activities contribute to the achievement of national sustainability goals. The study identifies government relations (GR) management tools that are instrumental in successful implementation of ESG practices and investigates the relationship between GR management as a formalized function and the effectiveness of sustainable develop ment practices in Russian companies. Stakeholder theory constitutes the methodological basis of the study. The key research methods are correlation analysis and one-way analysis of variance (ANOVA). The data set of the study is represented by data from 86 largest Russian companies from the RAEX TOP-100 ESG Ranking as of December, 2023. The top tier companies demonstrate better financial performance and tend to single out GR as a separate function (division). System relationships between big busi ness and the state produce an overall positive effect in society and allow achieving financial stability. The larger the business and the scale of a company’s ESG projects, the greater the need for coordinated actions to reduce potential risks and losses. At the same time, cross-functional interaction between GR and other divisions of the firm enhances the effectiveness of its ESG practices. The findings prove that implementing the GR function is important for both private businesses and companies partially owned by the state.